The Use of Serial Picture Media to Improve English Speaking Ability at SMP YPK Syaloom Klademak Sorong City - Gaspersz, Sherly; Uktolseja, Lulu Jola (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2020)
The purpose of this research is to see the improvement of English speaking ability of students at SMP YPK Syaloom Klademak Sorong City.Sample in this research centered on class VIIB. While the research instrument is serial picture media that is inserted into the learning device and used as a guide in learning. Therefore, an effective learning media is needed, namely serial picture media to hone the mindset and encourage students at SMP YPK Syaloom Klademak Sorong City to enrich vocabulary so that they can communicate using English fluently. This research uses Classroom Action Research (CAR) and uses the research model of Kemmis and Mc. Taggart is made into two cycles in which each cycle the researcher uses planning, action, observation and reflection. Thus the form taken is to look at pronunciation, grammar, vocabulary, comprehension, and fluency. Based on the research that has been done, it can be obtained that the research results have significant changes in the application of this learning media is 31% where the results of the implementation of serial picture media in the first cycle are categorized as good is 44% and the second cycle which is categorized as good is 75%. Thus students have the opportunity to improve their own quality, especially in increasing the ability to speak English with the learning media used by the teacher in the teaching and learning process.